2018
DOI: 10.14444/5050
|View full text |Cite
|
Sign up to set email alerts
|

The 2-Level Experience of Interlaminar Stabilization: 5-Year Follow-Up of a Prospective, Randomized Clinical Experience Compared to Fusion for the Sustainable Management of Spinal Stenosis

Abstract: Background: To alleviate the symptoms of lumbar spinal stenosis, widely accepted methods of surgical treatment include decompression alone and decompression with fusion. As an alternative to these methods, interlaminar stabilization (ILS) devices with decompression were introduced. There is a large amount of research dedicated to examining the efficacy of ILS devices in single-level procedures, but fewer studies focus on their efficacy in 2-level procedures. The purpose of this study was to compare decompressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…com/CJP/A846), while 32 (9.7%) reported that they tracked opioid use. However, of these 32, only 21 studies (6.4% of all studies) 41,[43][44][45][46][47]49,52,53,[56][57][58][60][61][62][63]65,[69][70][71][72] specifically reported opioid use out to at least 6 months (Table 2). Eleven of the 329 studies 42,48,50,51,54,55,59,64,[66][67][68] tracked opioid use before surgery or immediately after surgery but did not track opioids out at least 6 months.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…com/CJP/A846), while 32 (9.7%) reported that they tracked opioid use. However, of these 32, only 21 studies (6.4% of all studies) 41,[43][44][45][46][47]49,52,53,[56][57][58][60][61][62][63]65,[69][70][71][72] specifically reported opioid use out to at least 6 months (Table 2). Eleven of the 329 studies 42,48,50,51,54,55,59,64,[66][67][68] tracked opioid use before surgery or immediately after surgery but did not track opioids out at least 6 months.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Cohen's kappa for agreement among the independent reviewers for the title and abstract screen was moderate (k = 0.79) and for the full-text screen was almost perfect (k = 0.95). Detailed descriptions of the 21 studies 41,[43][44][45][46][47]49,52,53,[56][57][58][60][61][62][63]65,[69][70][71][72] that tracked longterm opioid use are provided in Table 2. There were 2286 pooled participants across all studies with a mean age ranging from 39.2 to 71.0 years, with 53.6% (n = 1226) female.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations